Relevansi Sikap dan Solusi Menghadapi Resesi Ekonomi dalam Surah Yusuf Perspektif Teori Double Movement Fazlur Rahman - Mufidah, Triwik; Huda, Muhammad Habib Zainul; Putra, Heldy Ramadhan (Sekolah Tinggi Agama Islam Sumatera Medan, 2023)
Various economic surveys from international financial institutions say, starting the year 2023 and year beyond, many countries are threatened by recession (economic slowdown), including Indonesia. Therefore, people must prepare the best possible attitudes and solutions in facing a recession, of course, in a way that is in accordance with Islamic teachings. In Islamic Dates, attitudes and solutions to face recession are always associated with the story of Nabi Yusuf (as), which is immortalized in Al-Qur’an Sura Yusuf. So that the purpose of this research is none other than to find the best relevant attitudes and solutions in facing the Recession through the content of Al-Qur’an Sura Yusuf uses the perspective of Fazlur Rahman's Double Movement Theory. The results : (1) A state official, should have the characteristics of Prophet Yusuf (as), namely, Makin (Have a good track record), Amin (Honest), Hafidz (Have Skills), and 'Aliim (Knowledgeable). 2). There are five attitudes that must be taken by society, by Individuals, by governments in the face of Recession. 3). The various economic policies of Prophet Yusuf are relevant for countries around the world in the face of economic recession. This research provides readers with recommendations on the insights of communities or individuals responding to economic recessions and developing strategies to overcome these challenges.